Examining the Competitive Advantage of Property Sales Agents in The Era of AI-Driven Digital Marketing - Banjar; Sya’roni, Deden Abdul Wahab (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This research hopes to test and analyze the influence of property sales agent competence on perceived competitive advantage and consumer purchasing intentions in the era of AI-based digital marketing, especially through CRM and chatbots. Researchers used a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze a sample of property consumers in Bandung. The research results state that sales agent competence has a significant influence on perceived competitive advantage and purchase intention, and cannot yet be completely replaced by AI or chatbot technology. Our research shows that human interaction, powered by the ability to understand consumer language and behavioral patterns (commonly associated with NLP), remains more effective than fully AI systems. Sales agent competency remains a key factor in property marketing performance, especially in Bandung, Indonesia. We can draw from the research results that integrating AI technology with human competence can increase marketing effectiveness and provide strategic value